MENINGKATKAN PERKEMBANGAN SOSIAL ANAK MELALUI PERMAINAN ULAR NAGA DI PAUD HARAPAN BANGSA KECAMATAN SINTUK TOBOH GADANG PADANG PARIAMAN - Mulya Syafrina (Universitas Negeri Padang, 2014)
The problem in this study is the low ability children in social development. The purpose of this study was to describe the social development of children in collaboration, responsibility and tolerance. This type of research used in this study is action research with children early childhood research subjects Nations Hope numbering 15 people. The instrument used is the observation and documentation formats. Data collection techniques are the techniques of observation and documentation. Analysis using a percentage formula. The results of this study indicate that hydra games can improve social development of children in collaboration, responsibility and tolerance seen from the average value at each statement of the first cycle and increased in the second cycle. This is proved by using hydra games can improve social development of children.